Evaluation of e-DDC Usage Among University Libraries in Bali - Ni Putu Premierita Haryanti; I Putu Suhartika (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2022)
This study examined how librarians at university libraries in Bali used e-DDC. This objective of the study was to ascertain how often e-DDC is used among university libraries and what factors affect that utilization. This study used a descriptive quantitative approach. All members of the library staff or librarians who had utilized e-DDC at university libraries in Bali made up the population and samples used in this study. Total sampling was the chosen sample method. The data were obtained through questionnaires, observations, and interviews. The findings of this study demonstrated that the library personnel preferred using printed DDC over electronic ones. As a result, they do not profit fully from using e-DDC. This was due to the fact that the information in printed DDC is more comprehensive than that in electronic form, making e-DDC utilization less than ideal. External factors like user training, accessibility, term clarity, and convenience of use affected how e-DDC was used. The DDC system must be re-maximized (upgraded) as a result, and the librarian or other library personnel must also be more receptive and adaptable to the current system in the library. The main purpose of using e-DDC is to make it simpler for users to find the needed classification numbers and to improve the processing section's unit.